Effects of diet and altitude on the microbiota of the first compartment of the stomach in Peruvian alpacas in highland puna regions and their correlations with blood parameters - Flores Huarco, Nils H. (2026)
This study explores the intestinal microbiota of eight 18-month-old male alpacas from two distinct high-altitude regions in Peru: the Wet Puna (4200 m above sea level) and the Dry Puna (4900 m above sea level). Using 16S rRNA and 18S rRNA metabarcoding, microbial communities of bacteria, archaea, fungi, and protists were analyzed from the first compartment of the stomach (C1) to investigate the diversity, taxonomic composition, and correlations with hematological parameters. Significant differences in microbial diversity and composition were observed between regions, driven by dietary and environmental factors. The Wet Puna exhibited greater alpha diversity in bacterial and fungal communities, while beta diversity highlighted distinct microbial compositions. Key taxa, such as Prevotella ruminicola and Acetitomaculum, were associated with energy metabolism and host adaptation, whereas methanogenic archaea (Methanobrevibacter, Methanosphaera) dominated in the Dry Puna, reflecting adaptations to arid conditions. Correlations between microbial taxa and hematological variables, such as Acetitomaculum with red blood cell count and Eremoplastron with neutrophil percentage, emphasize the complex interplay between microbiota and host physiology. These findings contribute to understanding microbial adaptations in high-altitude livestock and provide practical insights for enhancing alpaca management and conservation strategies through tailored nutritional approaches and sustainable grazing practices.